Scleritis and episcleritis. Issue 3 (March 1976) - Watson, P. G.; Hayreh, S. S.
Abstract : The data from 159 patients (217 eyes) with episscleritis and 207 patients (301 eyes) with scleritis have been investigated in detail and the results analysed with the help of a computer. Of these patients, 91 per cent were followed-up during a period of one to eight years. A new classification is presented which is as follows: Episcleritis (217 eyes) Simple episcleritis (170 eyes) Nodular episcleritis (47 eyes) Scleritis (301 eyes) Diffuse anterior scleritis (119 eyes) Nodular anterior scleritis (134 eyes) Necrotizing scleritis (42 eyes). Of these, 13 were regarded as scleromalacia perforans. Posterior scleritis (6 eyes) The diagnosis is based on an exact clinical examination which is fully described. Episcleritis has been shown to be a benign recurring condition, a mild keratitis being the only occasional complication. Episcleritis does not progress to scleritis, except in the case of herpes zoster which sometimes starts as an episcleritis with the vesicular stage of the eruption, to reappear three months later as a scleritis in the same site. No clear conclusions could be drawn as to the aetiology of episcleritis.